Automatic analysis of Android closed-source apps to support software engineering tasks : the mutation testing case (2019)
The amount of android applications is having a tremendous increasing trend, leading the mobile software market to exert pressure over practitioners and researchers about several topics like application quality, frequent releases, and quick fixing of bugs. Because of this, mobile app development process requires of improving the release cycles. Therefore, the automation of software engineering tasks has become a top research topic. As a result of this research interest, several automated approaches have been proposed to support software engineering tasks. However, most of those approaches that provide comprehensive results use source code as entry, which due to privacy factors imposes hard constraints on the implementation of those approaches by third-party services. Nevertheless, the market is leading practitioners to crowdsource/outsource software engineering tasks to third-parties that provide on-the-cloud infrastructures. Solutions that rely on third-party services cannot use state-of-the-art automated software engineering approaches because practitioners only provide them with APK files. Therefore, approaches that work at APK level...